Bound States of Dissipative Solitons in the Single-Mode Yb-Doped Fiber Laser - Xin He; Lei Hou; Mengmeng Li; Hongyu Guo; Baole Lu; Haowei Chen; Xinyuan Qi; Jintao Bai (IEEE Photonics Journal, 2016)
We present results of our research on the observation of a bound state of double dissipative-soliton operation of a passive mode-locked Yb-doped fiber laser based on the nonlinear polarization rotation mechanism through the proper adjustment of the wave plates. The generated dissipative solitons with large net positive cavity Group Velocity Dispersion (GVD) are characterized by their spectral profile of sharp peaks near edges, which are distinct from those of the conventional solitons in fiber lasers. By using an artificial saturable absorber, we have obtained stable single and double bound-state dissipative solitons. In all-normal-dispersion Yb-doped single-mode fiber lasers, the bound state of double dissipative solitons with a full-width at half-maximum of 7 ps, and a fixed pulse separation of 8 ps independent of the experimental conditions is achieved for the first time, to the best of our knowledge. Our result once again shows that the passively mode-locked fiber laser with large normal dispersion can help to explore dissipative soliton dynamics.